Production of a recombinant vaccine candidate against Burkholderia pseudomallei exploiting the bacterial N-glycosylation machinery - Garcia-Quintanilla, Fatima; Iwashkiw, Jeremy A.; Price, Nancy L.; Stratilo, Chad; Feldman, Mario F. (Frontiers in Microbiology, 2014)
Vaccines developing immune responses towards surface carbohydrates conjugated to proteins are effective in preventing infection and death by bacterial pathogens. Traditional production of these vaccines utilizes complex synthetic chemistry to acquire and conjugate the glycan to a protein. However, glycoproteins produced by bacterial protein glycosylation systems are significantly easier to produce, and could possible be used as vaccine candidates. In this work we functionally expressed the B. pseudomallei O polysaccharide (OPS II), the C. jejuni oligosaccharyltransferase (OTase), and a suitable glycoprotein (AcrA) in a designer E. coli strain with a higher efficiency for production of glycoconjugates. We were able to produce and purify the OPS II-AcrA glycoconjugate, and MS analysis confirmed correct glycan was produced and attached. We observed the attachment of the O-acetylated deoxyhexose directly to the acceptor protein, which expands the range of substrates utilized by the OTase PglB. Injection of the glycoprotein into mice generated an IgG immune response against B. pseudomallei, and this response was partially protective against an intranasal challenge. Our experiments show that bacterial engineered glycoconjugates can be utilized as vaccine candidates against B. pseudomallei. Additionally, our new E. coli strain SDB1 is more efficient in glycoprotein production, and could have additional applications in the future.